The Relationship Between Stock Market Performance and Its Liquidity - Hassani, Sara (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This thesis examines the macroeconomic determinants of stock market performance in Turkey during the period 1990-2019. Specifically, it examines the impact of gross domestic product, exchange rate, inflation and stock market liquidity on the performance of Turkish stock market. Currently, while theoretical and empirical literature revealed diverse views on the relationship between each determinant and stock market performance, no studies have been conducted with particular reference to the Turkish stock market given the significant role the Turkish market plays in the world. This thesis enriches existing literature by investigating the macroeconomic determinants of stock market performance in Turkey using the Johansen cointegration and VECM testing procedure. The results find that all our independent variables have a positive long-run impact on Turkish stock market performance. This thesis recommends that Turkish government has to sharpen the public expenditures through further investments. The Government of Turkey must attempt to keep its inflation rates at a stable level. Furthermore, the pivot of this thesis hovered around market liquidity therefore, having “larger capital markets” as well as allowing for “more technological innovation in trading” will contribute to intensification of the market liquidity which in turn can hone the Turkish stock market performance. Keywords: Stock Market Performance, Gross Domestic Product, Inflation, Stock Market Liquidity, Exchange Rate, Turkey.

ÖZ: Bu tez, 1990-2019 döneminde Türkiye'deki borsa performansının makroekonomik belirleyicilerini incelemektedir. Spesifik olarak, gayri safi yurt içi hasılası, döviz kuru, enflasyon ve borsa likiditesinin Türk hisse senedi piyasasının performansı üzerindeki etkisini incelemektedir. Şu anda, teorik ve ampirik literatür her bir belirleyici ile borsa performansı arasındaki ilişki ile ilgili farklı görüşler ortaya koyarken, özellikle Türk borsasına atıfta bulunan herhangi bir çalışma yapılmamıştır. Bu çalışma, Johansen eşbütünleşme ve VECM test prosedürünü kullanarak Türkiye'deki borsa performansının makroekonomik belirleyicilerini araştırarak mevcut literatürü zenginleştirmektedir. Sonuçlar, tüm bağımsız değişkenlerimizin uzun vadede olumlu bir etkiye sahip olduğunu bulmuştur. Bu tez, Türk hükümetinin daha fazla yatırım yaparak kamu harcamalarını keskinleştirmesi gerektiğini önermektedir. Türkiye Hükümeti enflasyon oranlarını istikrarlı bir seviyede tutmaya çalışmalıdır. Ayrıca, bu tezin ekseni piyasa likiditesi etrafında şekillenmiştir, bu nedenle, “daha büyük sermaye piyasalarına” sahip olmanın yanı sıra “ticarette daha fazla teknolojik yeniliğe” izin verilmesi, piyasa likiditesinin yoğunlaşmasına katkıda bulunarak Türk hisse senedi piyasası performansını artıracaktır. Anahtar Kelimeler: Menkul kıymetler borsası performansı, gayri safi yurt içi hasıla, enflasyon, borsa likiditesi, döviz kuru, Türkiye.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2021. Supervisor: Asst. Prof. Dr. Nigar Taşpınar.
Keywords: Banking and Finance; Stock Market--Liquidity; Stock Market Performance; Gross Domestic Product; Inflation; Stock Market Liquidity; Exchange Rate; Turkey